Cellulose, Hemicellulose, and Lignin Content of Two Varieties of Sorghum Straw (Sorghum bicolor L. Moench) in Various Types of Biosa - Koano, Irene Suryanti; Bahri, Syamsul; Sayuti, Muhammad; Mukhtar, Muhammad; Sahara, La Ode (Jambura Journal of Tropical Livestock Science, 2025)
Sorghum straw is a by-product of the sorghum plant that contains lignocellulosic fibers, such as cellulose, hemicellulose, and lignin, which play an important role in its use as animal feed. The fiber content of straw is influenced by genetic factors of the variety and the application of biofertilizers, including Biosaka made from legume plants. This study aims to evaluate the cellulose, hemicellulose, and lignin content of straw of two sorghum varieties (Numbu and Kawali) by administering three types of biosaka (Gamal leaves, Moringa leaves, and Indigofera leaves). The study used a 2 × 3 factorial randomized block design (RBD) with three replications, resulting in 18 experimental plots. The treatments consisted of Numbu (V1) and Kawali (V2) varieties, as well as biosaka Gamal leaves (B1), Moringa leaves (B2), and Indigofera leaves (B3). Data were analyzed using ANOVA and if there were significant differences, continued with the LSD test at the 5% level. The results showed that sorghum varieties significantly affected the cellulose content of straw (P<0.05), where the Kawali variety had higher cellulose than the Numbu variety. Biosaka treatment and variety × Biosaka interaction did not significantly affect the cellulose, hemicellulose, or lignin content (P>0.05). However, the combination of the Kawali variety with Gamal leaf Biosaka (V2B1) produced the highest cellulose content significantly. It can be concluded that the variety factor plays a greater role in determining the lignocellulose content of sorghum straw than the type of Biosaka given.